Androgen abuse among gay and bisexual men. Issue 6 (20th December 2021) - Griffiths, Scott; Jotanovic, Dejan; Austen, Emma
Abstract : Purpose of review: Androgen abuse is more prevalent among gay and bisexual (i.e. sexual minority) men than heterosexual men. We review recent research about androgen abuse in sexual minority men and provide relevant social, cultural, and historical contexts. Recent findings: Androgen abuse among sexual minority men is shaped by the intersections of sexuality, desirability, masculinity, and race. Muscular male bodies are desired and – in erotic settings especially – prized as literal embodiments of masculinity. Racist stereotypes unjustly diminish the desirability and masculinity of sexual minority men who belong to racial minorities, especially those who are Asian or Black, and the higher rates of androgen abuse among these racial minorities may reflect a compensatory motivation for these diminishments. The historical context for sexual minority men – decades of subjugation alongside stereotypes of masculinity-compromising effeminacy – further complicate the intersections of sexuality with androgen abuse. Harm minimization efforts led by empathetic endocrinologists stand the best chance of achieving positive outcomes for sexual minority men who use androgens. Summary: More dedicated research on androgen abuse among sexual minority men is needed as this population requires thoughtfully designed research that is incorporative – at a minimum – of the complexities of sexuality, desirability, masculinity, and race.